Estimating the contribution of stimulant injection to HIV and HCV epidemics among people who inject drugs and implications for harm reduction: A modeling analysis. (1st August 2020) - Cepeda, Javier A.; Vickerman, Peter; Bruneau, Julie; Zang, Geng; Borquez, Annick; Farrell, Michael; Degenhardt, Louisa; Martin, Natasha K.
Highlights: Stimulant injection contributes substantially to HIV and HCV transmission. High coverage needle/syringe programs can reduce disease burden due to stimulant use. Modeling findings were robust to stimulant turnover and preferential mixing. Abstract: Background: Stimulants, such as amphetamines and cocaine, are widely injected among people who inject drugs (PWID). Systematic reviews indicate stimulant injection is associated with HIV and HCV among PWID. Using these associations, we estimated the contribution of stimulant injection to HIV and HCV transmission among PWID. Methods: We modeled HIV and HCV transmission among PWID, incorporating excess injecting and sexual risk among PWID who inject stimulants. We simulated three illustrative settings with different stimulants injected, prevalence of stimulant injecting, and HIV/HCV epidemiology. We estimated one-year population attributable fractions of stimulant injection on new HIV and HCV infections, and impact of scaling up needle-syringe programs (NSP). Results: In low prevalence settings of stimulant injection (St. Petersburg-like, where 13 % inject amphetamine), 9% (2.5–97.5 % interval [95 %I]: 6–15 %) and 7% (95 %I 4–11 %) of incident HIV and HCV cases, respectively, could be associated with stimulant injection in the next year. With moderate stimulant injection (Montreal-like, where 34 % inject cocaine), 29 % (95 %I: 19–37 %) and 19 % (95 %I: 16–21 %) of incident HIV and HCV cases, respectively, could be associated with stimulant injection. In high-burden settings like Bangkok where 65 % inject methamphetamine, 23 % (95%I:10–34%) and 20 % (95%I: 9-27%) of incident HIV and HCV cases could be due to stimulant injection. High-coverage NSP (60 %) among PWID who inject stimulants could reduce HIV (by 22–65 %) and HCV incidence (by 7–11 %) in a decade. Discussion: Stimulant injection contributes substantially to HIV and HCV among PWID. NSP scale-up and development of novel interventions among PWID who inject stimulants are warranted.